Does finance causes economic growth in Africa? - Yusuf, Salama; Habibullah, Muzafar Shah; Mohamed, Azali; Lee, Chin (Faculty of Economics and Management, Universiti Putra Malaysia, 2012)
The paper examines the causal relationship between financial sector development and economic growth in34 African countries. Using the Panel Autoregressive Distributed Lag (PARDL) framework in line with Pesaran et al. (1999), the Pooled Mean Group (PMG) shows that there is the existence of a relationship between the financial sector and economic growth in Africa. There also exist bidirectional causality between financial sector development and economic growth. Thus implementation of policies to improve financial sector definitely going to have an impact on economic growth in the long run.